Educação do campo: um olhar para situações socioeconômico-financeiras na educação matemática - Ledur, Diandra Batirola (2022)
This research aims to analyze contexts explored by socioeconomic-financial situations in productions and textbooks of Countryside Education in the context of Mathematics Education. Therefore, a qualitative approach is adopted that follows the principles of content analysis, with the specific objectives of: mapping publications that take Countryside Education as their object in the annals of three editions of the National Meeting of Mathematics Education (ENEM); to characterize the PNLD Campo and the textbooks that compose it, identifying socioeconomic-financial situations in the everyday urban context, everyday peasant and interdisciplinary; to analyze activities that deal with socioeconomic and financial situations in six textbooks, intended for the 4º and 5º year of Elementary School, approved by PNLD Campo 2013 and PNLD Campo 2016. Among the results, it is evident that of the 49 works contained in the annals of ENEM, 10 productions emphasize contents of School Mathematics contextualized in everyday life, being that: four involve financial situations, as two address production and cost, one domestic and countryside economy, and one the idea of interest. In addition, two productions analyze books, but do not deal specifically with the PNLD Campo. When examining the Guide PNLD Campo 2013, the Guide PNLD Campo 2016 and the 4º and 5º year volumes of the “Projeto Buriti” (C1), “Campo Aberto” (C2) and “Novo Girassol” (C3) collections, C1 is classified as an integrated multidisciplinary series, while C2 and C3 are interdisciplinary series. In addition, C2 proposes articulation between the curricular components so that Mathematics is related to the Natural Sciences, in which both are physically presented together in all chapters, unlike C1 and C3, organized by curricular component. With regard to the socioeconomic-financial situations proposed in the six volumes, 21 prefixes identify 100 different activities, of which 49 belong to C1, 20 to C2 and 31 to C3. Through understandings about the context linked to interdisciplinarity, the urban daily life and the peasant daily life, it can be seen that the interdisciplinary context involves environmental themes, the historical evolution of numbers and currency changes; the everyday urban context, for the most part, emphasizes the recognition of banknotes and coins values and the calculation of the total cost in the acquisition of goods and services; everyday countryside context favor common rural practices such as raising chickens, selling food, values of rural areas and the use of money. Among the 100 activities analyzed, there are also contents of School Mathematics linked to the monetary system, with values belonging to the set of natural numbers, both to identify bills and to perform elementary operations, with or without the use of mental calculation strategies and estimated. Less frequently, activities involving rational numbers in decimal form are identified. In terms of representations, it appears that the statements of activities favor the use of natural language accompanied by numerical representations. In addition, there are some iconic representations such as, for example, tables, invoices, bank statements, advertising productions, bills and coins.